Sequence family variant loss from the AZFc interval of the human Y chromosome, but not gene copy loss, is strongly associated with male infertility. Issue 11 (1st November 2004) - Machev, N; Saut, N; Longepied, G; Terriou, P; Navarro, A; Levy, N; Guichaoua, M; Metzler-Guillemain, C; Collignon, P; Frances, A-M; Belougne, J; Clemente, E; et al.
Abstract : Background: Complete deletion of the complete AZFc interval of the Y chromosome is the most common known genetic cause of human male infertility. Two partial AZFc deletions (gr/gr and b1/b3) that remove some copies of all AZFc genes have recently been identified in infertile and fertile populations, and an association study indicates that the resulting gene dose reduction represents a risk factor for spermatogenic failure. Methods: To determine the incidence of various partial AZFc deletions and their effect on fertility, we combined quantitative and qualitative analyses of the AZFc interval at the DAZ and CDY1 loci in 300 infertile men and 399 control men. Results: We detected 34 partial AZFc deletions (32 gr/gr deletions), arising from at least 19 independent deletion events, and found gr/gr deletion in 6% of infertile and 3.5% of control men (p>0.05). Our data provide evidence for two large AZFc inversion polymorphisms, and for relative hot and cold spots of unequal crossing over within the blocks of homology that mediate gr/gr deletion. Using SFVs (sequence family variants), we discriminate DAZ1/2, DAZ3/4, CDY1a (proximal), and CDY1b (distal) and define four types of DAZ - CDY1 gr/gr deletion. Conclusions: The only deletion type to show an association with infertility was DAZ3/4 - CDY1a (p = 0.042), suggesting that most gr/gr deletions are neutral variants. We see a stronger association, however, between loss of the CDY1a SFV and infertility (p = 0.002). Thus, loss of this SFV through deletion or gene conversion could be a major risk factor for male infertility.